The Techno-aesthetic Hybrid - Cecchi, Dario (E|C, 2023)
The aims at reconstructing the concept of hybrid in a philosophical (critical) perspective. After reconstructing this concept in Bruno Latour's theory, the paper compares his theory with the reflections developed by the Italian thinker Emilio Garroni concerning the issue of the relationship between technics and creativity. These reflections are then coupled with Gilbert Simondon s theory of the technical objects, in order to develop insight into the nature of hybrids. According to this point of view, hybrids are not the result of posthumanism, but rather represent the very essence of human nature, as far as the latter is: a) fundamentally bound to technics; b) rooted into intersubjectivity; c) intrinsically evolutionary. Digital technologies, and abov e all the implementations of algorithms, are critically considered in the aforementioned vein, in order to unveil the new possible humanity they are designing.